Structure and sequence of the gene for the largest subunit of trypanosomal RNA polymerase III. - Köck, J (1988)
As the first step in the analysis of the transcription process in the African trypanosome, Trypanosoma brucei, we have started to characterise the trypanosomal RNA polymerases. We have previously described the gene encoding the largest subunit of RNA polymerase II and found that two almost identical RNA polymerase II genes are encoded within the genome of T. brucei. Here we present the identification, cloning and sequence analysis of the gene encoding the largest subunit of RNA polymerase III. This gene contains a single open reading frame encoding a polypeptide with a Mr of 170 kD. In total, eight encoding a polypeptide with a Mr of 170 kD. In total, eight highly conserved regions with significant homology to those previously reported in other eukaryotic RNA polymerase largest subunits were identified. Some of these domains contain functional sites, which are conserved among all eukaryotic largest subunit genes analysed thus far. Since these domains make up a large part of each polypeptide, independent of the RNA polymerase class, these data strongly support the hypothesis that these domains provide a major part of the transcription machinery of the RNA polymerase complex. The additional domains which are uniquely present in the largest subunit of RNA polymerase I and II, respectively, two large hydrophylic insertions and a C-terminal extension, might be a determining factor in specific transcription of the gene classes.